Transcription factor hypoxia-inducible factor (HIF)-1alpha is relevant for necrosis of Mycobacterium avium-induced granulomas. - M. Borges (2014)
Mycobacterial infections are characterized by the formation of granulomas. Granulomas are well-organized aggregates of immune cells, namely infected macrophages. The granuloma's main function is to constrain and prevent dissemination of the mycobacteria while concentrating the immune response to a limited area. In some cases these granulomas undergo central necrosis leading to their caseation, although the underlying mechanisms are still poorly understood. It has been reported that reduced vascularization of granulomas may be one essential mechanism for caseation and some studies have demonstrated severely hypoxic regions at the center of the granuloma. The hypoxia-inducible factor - 1alpha (HIF-1α) has been shown to be important in some diseases, such as cancer and infections. HIF-1α is able under hypoxic conditions to transcriptionally regulate gene expression, allowing macrophage adaptation to hypoxia [1]. The Appelberg laboratory has developed a granuloma necrosis model that mimics the human pathology of Mycobacterium tuberculosis, using C57BL/6 (WT) mice infected intravenously with a low dose of a highly virulent strain of Mycobacterium avium (ATCC 25291). Such mice develop granulomas that, at 4 months of infection, exhibit central necrosis [2]. To determine the relevance of HIF-1α during M. avium infection we used a mouse strain deleted of HIF-1α under Cre-lox system in the myeloid cell lineage (HIF1αKO). Infected mice were euthanized at different times during the infection and the lungs, liver and spleen were aseptically collected. Bacterial loads were determined in the organs of infected animals. Morphometric analysis of granulomas was performed in haematoxylin-eosin stained liver sections. The localization of macrophages in the livers from infected mice was studied by immunohistochemistry by evaluating the expression of F4/80. The analysis of liver and spleen cell populations were determined by flow cytometric analysis. IFN-gamma and HIF-1α production has been evaluated ex-vivo by ELISA. The results obtained indicate that HIF1α KO mice are more susceptible to the infection and the onset of necrotic granulomas is faster.